Morphologie verbale et FLE : les groupes verbaux en -ir - Nouveau, Dominique (My University, 2017)
This study looks at the acquisition of French conjugation by Dutch students doing their first year of French studies at the department of Romance languages. Twenty students were asked to perform a spoken task in which they had to fill in conjugated verbs in the present and past tense. The test items belonged to the three main verb classes and represented different verbs whose infinitive is -ir. Serious errors showed up more specifically in the conjugation of the regular verbs in the traditionally called second verb class. The high percentage of errors and the nature thereof were often related to a confusion of the stem. These results also revealed that students do not manage to discriminate and identify verb types. We make some pedagogical suggestions based on the outcomes. We investigate the potential of spoken corpora as resources to provide complementary learning materials for student activities. Interestingly, training the verbal morphology of French as a foreign language proves to be an excellent way to raise language awareness of common phonological processes.
Keywords: French as a foreign language; morphology; phonology; data driven learning